Bimetallic ZnFe2O4 nanosheets prepared via electrodeposition as binder-free high-performance supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Park, Chanwoo; Kim, Yongil; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
Binder-free bimetallic ZnFe2O4 nanosheets were fabricated using one-step electrodeposition, which facilitated excellent electrical contact between the ZnFe2O4 nanosheets and the nickel substrate. The resultant numerous ZnFe2O4 nanosheets with their cubic spinel structures promote interfacial activity to enhance the electrochemical and Faradaic redox reactions. The metallic Zn and Fe from the cubic spinel structure of ZnFe2O4 attract electrolytic ions and increase the energy-storage capability, thus yielding a specific capacitance of 1093 F.g(-1) at a current rate of 1 A.g(-1). Different samples were prepared by varying the amount of metal salts in the electrodeposition solution while maintaining a constant ZnNt:FeSO4 concentration ratio of 1:2 for all cases. The optimal electrode composition, which yielded an energy density of 54 Wh.kg(-1) and a capacitance retention of 93.5% at N = 5000 charge-discharge cycles, was identified.
Keywords: Bimetallic; Electrodeposition; Energy storage device; supercapacitor; ZnFe2O4 nanosheet

Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors

Flexible metallized carbon nanofibers decorated with two-dimensional NiGa2S4 nanosheets as supercapacitor electrodes - Kim, Yongil; Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Lee, Hae-Seok; Yoon, Sam S. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Herein, high-power flexible supercapacitor electrodes were fabricated by decorating Ni-electroplated carbon nanofibers (Ni@CNF) with two-dimensional NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets. The electrical conductivity of carbon nanofibers was enhanced by the addition of nickel, and the energy storage capability was enhanced by decoration with NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The impact of metal (Ni/Ga) ratio on the overall electrochemical performance of the supercapacitor was studied by varying the Ga concentration. The NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets promoted diffusion of the electrolyte into the electrode, thereby improving the electrochemical activity. The nanosheets also intensified the charge transfer rate within the composite electrode, which contributed to the overall improvement in the electrochemical performance. The optimal Ga concentration was the concentration at which the specific capacitance was the highest at 488 F·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> with a potential window of 1.1 V and current rate of 0.5 A·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The long-term stability test revealed that the capacitance retention of the electrode with this optimal Ni/Ga ratio was 109% after 20,000 cycles. This flexible supercapacitor electrode was subjected to 2000 bending cycles, and the corresponding cyclic voltammetry performance was assessed. In combination, the outstanding electrochemical performance and durable mechanical properties render the NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/Ni@CNF electrode highly suitable for flexible energy storage applications.

Electrospun zinc-manganese bimetallic oxide carbon nanofibers as freestanding supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yongil; Kim, Taegun; El-Newehy, Mohamed; Aldalbahi, Ali; Yoon, Sam S. (International Journal of Energy Research, 2022)
Flexible, lightweight, and freestanding zinc-manganese oxide carbon nanofibers are promising materials for the fabrication of portable electronic devices. Composite nanofibers were synthesized using terephthalic acid and sodium dodecyl sulfate. Terephthalic acid improves the flexibility of the composite fibers and facilitates the diffusion of electrolytic ions. Meanwhile, sodium dodecyl sulfate aids to elevate the metal (zinc) oxide particles to the surface of the nanofibers during annealing. The texturing of the carbon nanofiber surface with ZnO enhances the electrochemical activity of the composite fibers. Parametric studies were conducted by varying the weight ratio of zinc and manganese acetates from zero to unity. The optimal case with a ratio of 0.75 produces specific capacitances of 1080 and 817 F center dot g(-1) at current densities of 1 and 10 A center dot g(-1), respectively, with a wide potential window of 1.6 V, indicating outstanding energy storage capabilities. The capacitance retention was 92% after 10 000 galvanostatic charge-discharge cycles. The bending angle test confirmed the mechanical durability of the freestanding carbon nanofiber electrodes, and the corresponding change in the cyclic voltammetry curve was negligible.
Keywords: electrospinning; freestanding electrode; high-energy-density; supercapacitor; ZnMn2O4